Socialization of the Use of Linktr.ee E Lactation Counseling for Breastfeeding Village Cadres, Wonokromo Village, Surabaya - uke maharani dewi; Fauziyatun Nisa'; Aisyah Aisyah; Suci 'Abidah (UNUSA Press, 2022)
The Covid-19 pandemic has burdened the implementation of lactation counseling services directly by cadres to POSYANDU targets. This community service aims to educate cadres in Kampung ASI Wonokromo about how to use lactation counseling e media so that counseling services can be carried out online. Forty cadres of Kampung ASI were given socialization on using e-counseling media. Socialization is carried out utilizing practice or simulation of online e-counseling media through zoom meetings. This activity was carried out for 2 weeks, from June to October 2021. Evaluation of the implementation of the activities was carried out through pre- and post-tests using a questionnaire. 93% of cadres said that linktree e-lactation counseling was easy to use. A total of 97.4% said that linktree e-lactation counseling made it easier for cadres to provide online counseling. Linktr.ee e lactation counseling supports lactation counseling services in Kampung ASI, Wonokromo Village during the Covid-19 pandemic. It is expected that in future activities cadres can gain skills in making e-counseling media to develop media independently according to their needs.